A traversal multi-target path planning method for multi-unmanned surface vessels in space-varying ocean current. (15th June 2023) - Yu, Jiabin; Chen, Zhihao; Zhao, Zhiyao; Yao, Peng; Xu, Jiping
Abstract: Multi-target traversal is an important aspect of research on multiple unmanned-surface-vehicle (USV) cooperation in the space-varying ocean current environment. Here, we propose a traversal multi-target path-planning method for multi-USVs in space-varying ocean current. The proposed algorithm has two steps. To solve the problem of task allocation, we propose a traversal multi-target path planning method for multi-unmanned surface vessels in space-varying ocean current. The improved Hungary algorithm is used for multi-target allocation. To solve the problem of path planning, we propose a virtual field RRT* (VF-RRT*) algorithm. The virtual field sampling algorithm and the ocean current constraint function are introduced in the RRT* algorithm. To verify the effectiveness of the algorithm, we implemented three groups of simulation experiments. The results show that the planning path of the proposed algorithm was more reasonable, indicating that the proposed algorithm is effective in path planning and task allocation. Highlights: A task allocation method for multi-targets traveling is proposed. A virtual field RRT* (VF-RRT*) algorithm is proposed. Improving the efficiency of multi-target task allocation. Improving the effectiveness of RRT algorithm in the ocean current environment.